Creative Leadership of the School Administrators Affecting the Operations of Student Development Activities in Schools under the Pattani Primary Educational Service Area Office 3 - Hohma, Yusree; Wannapairo, Suntaree (Journal of Graduate Research, 2025)
This research aimed to: 1) study the creative leadership of school administrators; 2) study the student development activities; 3) examine the relationship between creative leadership and student development activities in schools; and 4) create an equation predicting the creative leadership of school administrators affecting the operation of student development activities in schools. The sample consisted of 297 participants. The research instrument was a questionnaire. Statistical methods used in the study included percentage, mean, standard deviation, Pearson’s correlation coefficient, and multiple regression analysis. The research findings were as follows: 1) The overall level of creative leadership among school administrators was high, with teamwork receiving the highest mean score. 2) The overall implementation of student development activities in schools was also at a high level, with student activities (such as scouting, girl guides, and Red Cross Youth) receiving the highest mean score, 3) The correlation between creative leadership and student development activities in schools was significantly positive at the 0.01 level, with a correlation coefficient of 0.865. 4)The predictive analysis of creative leadership affecting student development activities identified four key variables: flexibility, teamwork, problem-solving, and creativity, all of which were statistically significant at the 0.01 level. These variables collectively explained 75% of the variance. The multiple regression equation can be expressed as follows: Raw score Ŷ = 0.699 + 0.244 (x2) + 0.225 (x3) + 0.205 (x5) + 0.164 (x4) and Standard score Ẑ = 0.236 (x5) + 0.252 (x2) + 0.252 (x3) + 0.188 (x4)